Simulation Study on Supercontinuum Generation at Normal Dispersion Regime of a Carbon Disulfide-core Photonic Crystal Fiber - Chu Van, Bien; Quang Ho, Dinh; Thi Ha, Le; Cao Long, Van; Van Hung, Vu; Le Van, Hieu (Communications in Physics, 2021)
A photonic crystal fiber with a hollow core filled with carbon disulfide (CS2) is proposed as a new source of supercontinuum light. We numerically study guiding properties of modeled fibers including the dispersion and the effective mode area of the fundamental mode. As a result, octave spanning of the SC spectrum was achieved in the wavelength range of near-IR from 1.25 μm to 2.3 μm with 90 fs pulse and energy of 1.5 nJ at a pump wavelength of 1.55 μm. The proposed fibers are fully compatible with all-silica fiber systems, in particular, could be used for all-fiber SC sources and new low-cost all-fiber optical systems.